An Analysis of The Implementation of Creating Shared Value (CSV) in Efforts to Fulfill Human Rights Among Communities Affected by A Company’s Operational Activities - Larevta Rommel Aldieno (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
The operational activities of companies in sectors such as mining, industry, infrastructure, and energy frequently generate social, economic, and environmental impacts on surrounding communities. In many cases, conventional Corporate Social Responsibility (CSR) programs are considered insufficient because they are often temporary, philanthropic, and not integrated into long-term business strategies. Therefore, the concept of Creating Shared Value (CSV) has emerged as a strategic approach that combines business sustainability with the improvement of social welfare. This research aims to analyze the implementation of CSV in fulfilling human rights among communities affected by corporate operational activities and to examine the benefits of CSV for both society and companies. This study employed a qualitative library research method using secondary data obtained from laws and regulations, scientific journals, textbooks, and relevant scholarly publications. The data were analyzed using qualitative descriptive analysis to interpret the relationship between CSV implementation, legal responsibility, and human rights fulfillment. The findings indicate that CSV is a conceptual development of CSR that positions social issues as strategic business opportunities rather than burdens. CSV contributes to economic empowerment, employment opportunities, education, social welfare, and the protection of cultural rights within affected communities. In addition, CSV provides benefits for companies through cost efficiency, productivity improvement, stronger stakeholder relations, and sustainable competitive advantage. In conclusion, CSV serves as an effective strategy to integrate corporate interests, social responsibility, and human rights fulfillment into sustainable business practices.